In Situ Association of Calvin Cycle Enzymes, Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase Activase, Ferredoxin-NADP+ Reductase, and Nitrite Reductase with Thylakoid and Pyrenoid Membranes of Chlamydomonas reinhardtii Chloroplasts as Revealed by Immunoelectron Microscopy. - Suss, K. H. (1995)
The in situ localization of the chloroplast enzymes ribulose-1,5-bisphosphate carboxylase (Rubisco), Rubisco activase, ribose-5-phosphate isomerase, glyceraldehyde-3-phosphate dehydrogenase, aldolase, nitrite reductase, ferredoxin-NADP+ reductase, and H+-ATP synthase was studied by immunoelectron microscopy in Chlamydomonas reinhardtii. Immunogold labeling revealed that, despite Rubisco in the pyrenoid matrix, Calvin cycle enzymes, Rubisco activase, nitrite reductase, ferredoxin-NADP+ reductase, and H+-ATP synthase are associated predominantly with chloroplast thylakoid membranes and the inner surface of the pyrenoid membrane. This is in accord with previous enzyme localization studies in higher plants (K.H. Suss, C. Arkona, R. Manteuffel, K. Adler [1993] Proc Natl Acad Sci USA 90: 5514-5518). Pyrenoid tubules do not contain these enzymes. The pyrenoid matrix consists of Rubisco but is devoid of the other photosynthetic enzymes investigated. Evidence for the occurrence of two Rubisco forms differing in their spatial localization has also been obtained: Rubisco form I appears to be membrane associated like other Calvin cycle components, whereas Rubisco form II is confined to the pyrenoid matrix. It is proposed that enzyme form I represents an active Rubisco when assembled into Calvin cycle enzyme complexes, whereas Rubisco form II may be part of a CO2-concentrating mechanism. Pyrenoidal Calvin cycle complexes are thought to be highly active in CO2 fixation and important for the synthesis of starch around the pyrenoid.